Peter Basseler - Basseler, Peter, 1947- (Edition Axel Menges, 2002)
"Peter Basseler, who lives in Berlin and Chicago, stands alone in the contemporary art landscape. The small-scale showcases, produced by a time-consuming process (sometimes taking over a year) since 1970, cannot be allotted to any particular trend. They have nothing in common with the Modern movement's object cases, they are not assembled from found items, not "ready mades", but have their roots in pre-Modernism - if anywhere." "There is nothing prefabricated in Basseler's showcases: everything has to be designed and made for a particular scenario, right down to the smallest detail. The thumb-high figures' gestures and facial expressions are central to the effect of the scene as a whole, and fascinating in their psychological refinement and their craftsmanship.".